Growth of bush pepper (Piper nigrum L.) plants as influenced by light and nutrients - Chandini, Madhura Devadas, S (Journal of Spices and Aromatic Crops, 2000)
Experiments conducted at Sadanandapuram (Kerala, India) to study the influence of nutrients under different light intensities on growth of bush pepper (Piper nigrum) plants indicated that better expression of growth characters was observed at 50% light intensity in plants given 37.5 g each of nitrogen and phosphorus and 50.0 g of potassium per year.